Electronic principles - Malvino, Albert Paul (McGraw-Hill Education, 2015)
Offers students a definitive overview of electronic circuits and devices. In this book, expert knowledge of electronic devices is presented with emphasis on modern integrated circuit (IC) technology. It offers coverage of basic electronics concepts, and applies these to the important electronic circuits and devices used in today's industry